Diverse cultures at work: ensuring safety and health through leadership and participation (Bilbao, 2013)
"This report describes the state of the art in addressing cultural diversity in the workplace, for which we distinguish two aspects: - Cross-cultural aspects in occupational safety and health (OSH): working in teams that are homogeneous with regard to their national culture. This issue is particularly interesting for multinational corporations and their expatriate managers: see, for example, culture comparison research from Hofstede and GLOBE (the Global Leadership and Organizational Behavior Effectiveness Research Project). - Multicultural aspects in OSH: this is managing OSH in multicultural (heterogeneous) workforces, working at one location or in one organisation. The differences between cultures are helpful in understanding discrepancies when several nationalities are working together. Cross-cultural (i.e. intercultural) studies describe characteristics of cultures and differences between different cultures. Therefore, the cross-cultural literature is very helpful in describing general differences that may occur in multinationals, as well as in multicultural teams. In this report the focus is on managing cultural diversity, i.e. general aspects of leadership and participation that benefit multicultural work teams. In this report formal organisational leadership is defined as leadership constituting a process of social influence that is enacted by designated individuals who hold a formal leadership role in organisations."